How heterogeneous are the determinants of total factor productivity in manufacturing sectors? Panel-data evidence from Vietnam - Quang Thanh Ngo; Quang Van Tran; Tien-Dung Nguyen; Trung Thanh Nguyen (Economies, 2020)
One of the remaining challenges in explaining differences in total factor productivity is heterogeneity between sectors and within a specific sector in terms of labor and capital. This paper employs the generalized method of moments (GMM) to identify factors that affect total factor productivity across 21 manufacturing sectors and to clarify the heterogeneous determinants of total factor productivity within manufacturing sectors for the period 2010-2015. Our estimations show that large firms have significantly greater total factor productivity levels than small firms in some fragmentations of firms in terms of both labor and total capital and in some manufacturing sectors. It is suggested that firm characteristics should be considered by the government in establishing relevant policies for enhancing firm productivity.
Keywords: L25; O33; L60; C33; 330; total factor productivity; panel causality; heterogeneity; manufacturing sector; Vietnam